2010
DOI: 10.1084/jem.20091299
|View full text |Cite
|
Sign up to set email alerts
|

BCL6 is critical for the development of a diverse primary B cell repertoire

Abstract: BCL6 protects germinal center (GC) B cells against DNA damage–induced apoptosis during somatic hypermutation and class-switch recombination. Although expression of BCL6 was not found in early IL-7–dependent B cell precursors, we report that IL-7Rα–Stat5 signaling negatively regulates BCL6. Upon productive VH-DJH gene rearrangement and expression of a μ heavy chain, however, activation of pre–B cell receptor signaling strongly induces BCL6 expression, whereas IL-7Rα–Stat5 signaling is attenuated. At the transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
94
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 46 publications
3
94
0
1
Order By: Relevance
“…Therefore, we do not exclude the possibility that the ZIP10-Zn signaling axis simultaneously modulates the related signaling pathways. A Zn finger transcriptional factor BCL6 is critical for cell survival at the pre-B-cell transitional stage (41). In addition, E2A is also essential for B-cell development, and its absence results in growth arrest (42) and caspase-dependent apoptosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we do not exclude the possibility that the ZIP10-Zn signaling axis simultaneously modulates the related signaling pathways. A Zn finger transcriptional factor BCL6 is critical for cell survival at the pre-B-cell transitional stage (41). In addition, E2A is also essential for B-cell development, and its absence results in growth arrest (42) and caspase-dependent apoptosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be investigated whether JAB1 enhances Bcl6 translation and/or protein stability. A recent study showed a critical role for Bcl6 in early B cell development (44). We speculate that the observed B cell development block might be partially caused by a putative absence of Bcl6 in JAB1-deficient early B cells.…”
Section: Discussionmentioning
confidence: 62%
“…formation of a normal, diverse polyclonal repertoire (Duy et al, 2010). Bcl-6 can also facilitate osteoblastogenesis by recuperating the Runx2 nuclear translocation inhibited by STAT1 and can suppress osteoclastogenesis by attenuating NFATc1 target gene transcription (Fujie et al, 2015;Miyauchi et al, 2010).…”
Section: Reciprocal Interaction Between Immune System and Skeletal Symentioning
confidence: 99%
“…Bcl-6 can also facilitate osteoblastogenesis by recuperating the Runx2 nuclear translocation inhibited by STAT1 and can suppress osteoclastogenesis by attenuating NFATc1 target gene transcription (Fujie et al, 2015;Miyauchi et al, 2010). Bcl-6 / mice exhibit a distinct OP phenotype, with a markedly reduced new immature B cell pool in the bone marrow and impaired clonal diversity (Duy et al, 2010;Miyauchi et al, 2010 (Despars et al, 2013;Hamerman et al, 2005).…”
Section: Reciprocal Interaction Between Immune System and Skeletal Symentioning
confidence: 99%